Teaching computing a practitioner's perspective - Walker, Henry M. (Chapman & Hall/CRC textbooks in computing, 2018)
Combining over 20 years of articles written by the author for the SIGCSE Bulletin and Inroads, as well as new material, this comprehensive guidebook provides a wide range of teaching strategies, tips, and insights for computing educators. Designed for both new and experienced computing faculty at the undergraduate and graduate level, the book will serve as a practical, easy-to-use resource, covering a wide range of topics in a collection of focused down-to-earth chapters.